Relationship between human resource practices and employee engagement among employees in Schlumberger (M) Sdn Bhd, Damansara. - Shamini, Ragoo (2019)
Employee engagement plays a crucial role for career development. Similarly, HR Practices direct and indirectly influence employee performance. The aim of the study is to determine the relationship between Human Resource (HR) Practices and employee engagement of the employees at Schlumberger (M) Sdn Bhd, Damansara. The research framework contained three independent variables, namely compensation, career growth and training and development. The dependent variable of this study is employee engagement. Using self-administrative question this study involve 124 employees who are attached in Schlumberger (M) Sdn Bhd. The raw data from respondent were subjected to the Statistical Package for Social Sciences (SPSS) version 23. Correlation and regression analysis were applied to answer the objective of this study. Regression analysis revealed that there are significant relationship between HR Practices and employee engagement. As in the breakdown of the dimension, career growth and training and development has a significant relationship towards employee engagement however compensation relationship towards employee engagement towards employee engagement is not significant enough. It is hoped this study will help to identify other HR Practices factors contributing to employee engagement in an organization. Future research should include a larger number of organizations in other oil and gas industries.